Complete chloroplast genome of the economically important crop, Amorphophallus konjac (Araceae). Issue 1 (2nd January 2019) - Liu, Changkun; Yang, Lifang; Yang, Zhenyan; Ji, Yunheng
Abstract: Konjac ( Amorphophallus konjac K. Koch) is a perennial herb with high commercial and medicinal values. To better understand its genetic and genomic profiles, we sequenced and assembled the completed chloroplast genome of A. konjac. The complete chloroplast genome is 155, 277 bp in length, consisting of the large (LSC, 85, 412 bp) and the small single-copy region (SSC, 19, 449 bp), which were separated by a pair of inverted repeat regions (IRs, 25, 208 bp). It possesses 113 unique genes (80protein-coding genes, 29 tRNAs and 4rRNAs). Phylogenetic analysis suggests that A. konjac is closely related to Colocasia esculenta and Pinellia ternata .